Primary Intimal (Spindle Cell) Sarcoma of the Heart: A Case Report and Review of the Literature. (8th January 2013) - Ibrahim, A.; Luk, A.; Singhal, P.; Wan, Bo; Zavodni, A.; Cusimano, R. J.; Butany, J.
Abstract : Intimal (spindle cell) sarcomas of the left atrium are extremely rare primary cardiac tumours with three cases reported (Li et al. (2013), Cho et al. (2006), and Modi et al. (2009)). We present a 69-year-old man who first came to medical attention after experiencing abdominal discomfort. He had a 30 lb weight loss apparently due to dieting. He denied any other constitutional symptoms. His symptoms persisted despite a course of antibiotics for presumed diverticulitis. Laboratory values were within normal limits, though the haemoglobin was 131 g/L (normal: 140–180). Subsequent abdominal computed tomography (CT) scan revealed an abdominal wall mass and intracardiac lesion; the cardiac mass was further characterized by transesophageal echo (TEE), magnetic resonance imaging (MRI), and dedicated cardiac CT. TEE revealed a mass attached to the posterolateral wall of the left atrium above the mitral annulus, and the cardiac CT and MRI confirmed the TEE findings. The patient underwent extensive surgical resection and repair of the left side of the heart. Postoperatively, he developed acute renal failure requiring dialysis and reintubation for volume overload. He became acutely hypotensive, developed multiorgan failure, and succumbed to his illness. Histopathologic examination of the left atrial mass showed an intimal sarcoma.